Reflections on the changing nature of administrative space - Max Barlow (Belgeo)
Over the past twenty years or so globalization has become a catch-all term for all manner of change in society. At the same time, extension of the nation-state system to all parts of the world has been virtually completed, and thus forms a universal governmental framework within which processes of globalization are mediated. Although various global forces have tended to undermine the independence of national governments, the nation-state remains the fundamental framework within which the public sector operates and finds itself facing the challenges of a globalizing world. For the public sector, as in the corporate sector, restructuring (rolling back the state, reinventing government) has become a standard response. This paper reflects on one element of the state, administrative space, in relation to globalization and state restructuring. It discusses the nature of administrative space, and outlines some implications arising from developments associated with globalization (the development of supranational authorities and institutions, the fading influence of international boundaries, the emergence of new regional spaces) and state restructuring.